2016
DOI: 10.1007/s00737-016-0667-8
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of anxiety and mood in healthy late-reproductive-stage women with regard to hormonal and genetic factors

Abstract: The purpose of this study was to determine whether anxiety and mood disorders in late-reproductive-stage women are related to the serotonin transporter and monoamine oxidase A gene polymorphisms. Research instrument used in this study were the State-Trait Anxiety Inventory and the UWIST Mood Adjective Checklist. The 44-bp VNTR polymorphism in the 5-HTT (SLC 6A4) promoter region and the 30-bp VNTR polymorphism in the MAO-A promoter region were analyzed. The study included 345 healthy Polish women in the late re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Anxiety, irritability, and mood swings were commonly reported by LRS women in the POAS cohort, but a similar proportion of participants reported these mood symptoms across the MT stages 27 . Women in the West Pomerania Study also reported anxiety and mood disorders during the LRS 8 . A significantly higher proportion of WLB participants in the MT+ group reported low feelings compared to the LRS group.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Anxiety, irritability, and mood swings were commonly reported by LRS women in the POAS cohort, but a similar proportion of participants reported these mood symptoms across the MT stages 27 . Women in the West Pomerania Study also reported anxiety and mood disorders during the LRS 8 . A significantly higher proportion of WLB participants in the MT+ group reported low feelings compared to the LRS group.…”
Section: Discussionmentioning
confidence: 82%
“…27 Women in the West Pomerania Study also reported anxiety and mood disorders during the LRS. 8 A significantly higher proportion of WLB participants in the MTþ group reported low feelings compared to the LRS group. Depressed mood symptoms were seen in 50% of women in the premenopausal stage and increased to 60% SYMPTOMS DURING THE LATE REPRODUCTIVE STAGE in the late premenopausal stage for POAS participants.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation